Effects of selected chemical admixtures on physical and mechanical properties of cement mortar - Bethe, SS; Haque, MN; Islam, MR (Progressive Agriculture, 2020)
This study was aimed to determination of appropriate dosage of selected chemical admixtures to reduce water cement ratio for mortar mix also to determine its effects on physical and mechanical properties of cement mortar. Amount of water used in concrete is very important for the physical and mechanical properties. Less amount of water increase the strength but reduce the workability. Water retarding admixture can reduce the water cement ratio with desired workability. In this experiment plasticizer (master pel 707) and super plasticizer (master polyheed 8632) was used. The used dosages of admixture were 0.5%, 1% and 1.5% according to cement weight. The test was done at 3 days, 7 days, 28 days and 91 days. 2.76″ cube mold was used for the work. The experiment was done to find the difference between with and without admixture used in mortar. Water used reduced with add of plasticizer and super plasticizer. In the experiment the workability of normal mortar and admixture used mortar remain same. The compressive strength is high for 1.5% super plasticizer used sample. So 1.5% super plasticizer is recommended for high strength. Progressive Agriculture 30 (3): 305-310, 2019